Old social risk in a new light - the old age - Novak, Mojca (Družboslovne razprave, 2000)
Increasing gap between the working cohort and the retired one gave rise to substantial social and economic problems in the last decades. Reconsideration of the present retirement schemes revealed them as becoming incompatible with current structural changes, which calls for changing particularly the work contract and the welfare contract in operation. Many students of the old age issue advocate the idea that the old age and retirement per se stopped to be the principal risk for this cohort. While testing this assumption by employing the Slovene empirical evidence, the author concludes as follows: 1.The acquired education and occupation primarily determines the household's income while gender and age show no significant influence in this respect; 2.In comparison to the employed, retired might live in worse living conditions, but the relation of the latter with retirement is either weak or absent; 3. Living conditions satisfaction lacks any relation to living conditions themselves. Summing up, the old age and retirement fail to increase the risk of impoverishment, which fits to findings of certain other scholars, too.
Keywords: družbena diferenciacija; stari ljudje; staranje; upokojitev; življenjski standard; revščina; socialna varnost